WOMEN IN BLOCKCHAIN: DISCOURSE & PRACTICE IN THE CO-CONSTRUCTION OF GENDER AND EMERGING TECHNOLOGIES - Frizzo-Barker, Julie A. (AoIR Selected Papers of Internet Research, 2020)
Blockchain is an emerging technology characterized by peer-to-peer value transfer, decentralization, and democratic ideals of consensus. It also has a stark gender problem, with women representing just 14% of those participating in the space. This paper is based on 30 semi-structured interviews with women who work in blockchain, and participant observation at 17 blockchain meetups and conferences. The gendered discourses and practices surrounding blockchain events provide a productive site for examining the social construction of technologies, and more specifically the gendered social shaping of technologies. I use the theoretical lens of technofeminism, which strikes a balance between technophilia and technophobia, to explore the complex ways in which women’s everyday lives and technological change interrelate in the age of digitization. This co-construction approach challenges the prevailing discourses of technologies like blockchain as neutral and value-free. The goal of my study is not to ask or answer questions such as, “why aren’t there more women in blockchain?” or “how can we attract more women into blockchain?” Rather, I examine the gendered sociotechnical relations surrounding blockchain, as exemplified by discourses and practices at meetups and conferences. For instance, ‘by women, for women’ blockchain meetups serve as important spaces of resistance and support, whereas ‘women in blockchain’ panels at blockchain conferences ring hollow as ‘inclusive’ gestures, instead highlighting the exclusive culture at play. My findings explore how women’s identities and experiences are both enabled and constrained, often simultaneously, through participation in the blockchain space.